Pectinase Production and Clarification Treatments of Apple (Malus Domestica) Juice - Berutu, Cocok Ana Maryani; Fahrurrozi, Fahrurrozi; Meryandini, Anja (ANNALES BOGORIENSES, 2017)
Pectinases are a group of an enzyme that break down pectin, a polysaccharide that is found in plant cell walls. Today, the application of pectinolytic enzymes plays an important role in food technology for the maceration of fruits and vegetables, including for the extraction and clarification of juice. This research aimed to produce pectinase enzyme for clarifying of apple juice. A microbial culture was selected from cocoa bean fermentation samples and identified as Bacillus sp.. The highest enzyme activity was investigated after 48 hours of incubation. Citrus pectin as the carbon source and peptone as the nitrogen source was found as the best component for pectinase production. The optimum condition of pectinase activity was observed at pH 5, temperature 40 Â°C and the crude enzyme had the higher activity at one hour storage. Apple juice was treated with the enzyme at different concentrations (0%, 0.5%, 1%, 2%, 4%). Apple juice clarification was evaluated for its percent clarity and viscosity. The result showed that enzyme treatment at 4% in apple juice promoted juice clarification and decreased pH and viscosity. In conclusion, the quality of apple juice can be improved by enzymatic treatment using pectinase.